Tableware containing micro-foaming material and preparation method thereof

By using sandwich structure in disposable tableware and using micro-foaming materials as the intermediate layer, the existing tableware has solved the problems of high energy consumption, difficulty in degradation and insufficient insulation performance in the production process, and the lightweight and insulation performance of tableware has been achieved.

CN119872030APending Publication Date: 2025-04-25SUZHOU H & FINE PLASTIC CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411750294.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Existing disposable plastic tableware consumes a lot of energy during the production process and is difficult to degrade, which puts a burden on the environment. At the same time, its thermal insulation performance is insufficient, polyethylene tableware has poor deformation resistance and is prone to deformation and "collapse".

Method used

A tableware design with a sandwich structure, in which the middle layer is a micro-foaming material and the inner and outer layer is homopolypolypropylene or polyethylene. By combining copolymerized polypropylene and POE foamed masterbatches, a micro-foamed polypropylene or cycloolefin copolymer with lightweight and high thermal insulation properties is prepared.

Benefits of technology

It achieves the lightweight and thermal insulation performance of tableware, while maintaining the rigidity and toughness of polyethylene/polypropylene, reducing production energy consumption and environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119872030A_ABST
    Figure CN119872030A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of foaming materials, and discloses tableware containing a micro-foaming material and a preparation method thereof.The tableware comprises an inner layer, an outer layer and a sandwich layer, the sandwich layer is made of the micro-foaming material, and the inner layer and the outer layer are made of homo-polypropylene or polyethylene. The micro-foaming material is prepared from the following raw materials in parts by weight: 100 parts of co-polypropylene / COC particles and 30 to 60 parts of POE (Polyolefin Elastomer) foaming master batch, the POE foaming master batch is prepared from the following raw materials in parts by weight: 100 parts of POE particles, 6-15 parts of food-grade sodium bicarbonate and 3-10 parts of fatty alcohol-polyoxyethylene ether. The tableware is of a sandwich structure, the middle layer is made of the foaming material, the inner layer and the outer layer are made of homo-polypropylene or polyethylene, the physical properties such as rigidity and toughness of the homo-polypropylene or polyethylene can be given to the disposable tableware, the tableware has the light weight characteristic of the foaming material, and meanwhile the heat preservation performance of the tableware can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention belongs to the technical field of foaming materials, and in particular relates to tableware containing micro-foaming materials and a preparation method thereof. Background technology:

[0002] Disposable plastic tableware is a convenient and fast catering packaging container, which is widely used in various catering places, including fast food restaurants, canteens, take-out services, etc. Polypropylene is a non-toxic and odorless thermoplastic resin, which has good heat resistance, is not easy to react chemically with acid and alkali components in food, has low density, light weight, good toughness, high strength and other advantages; polyethylene material is also a non-toxic and odorless thermoplastic resin, which has good chemical stability and good low temperature resistance. Therefore, polypropylene and polyethylene are widely used in disposable lunch boxes.

[0003] At present, most of the materials of disposable tableware are made of single-layer or multi-layer high-rigidity homopolymer polypropylene, or single-layer or multi-layer polyethylene (PE). According to incomplete statistics, the annual consumption of disposable tableware is tens of billions. With the continuous increase in the use of disposable lunch boxes, many problems have been raised to be solved. One of them is that disposable tableware consumes a lot of energy in the production process, and the waste generated is difficult to degrade in nature, which brings some burden to the environment. The second is that the thermal insulation performance of the current disposable polypropylene tableware needs to be strengthened, while the polyethylene tableware has poor deformation resistance and is easy to deform and "collapse" under stress.

[0004] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention:

[0005] The object of the present invention is to provide a tableware containing micro-foam material and a preparation method thereof, so as to overcome the above-mentioned defects in the prior art.

[0006] In order to achieve the above object, the present invention provides a tableware containing micro-foam material, comprising an inner layer, an outer layer and a sandwich layer, wherein the sandwich layer is a micro-foam material, and the inner layer and the outer layer are homopolymer polypropylene or polyethylene.

[0007] Further, as a preference, the homopolymer polypropylene has a melt flow rate of 2.0 g / 10 min-3.0 g / 10 min, a tensile strength of 30-40 MPa, an elongation at break greater than 50%, and an impact strength of 6-8 kJ / m 2 .

[0008] Further, as a preference, the micro-foam material is micro-foamed polypropylene or micro-foamed cycloolefin copolymer; the micro-foamed polypropylene is composed of the following raw materials in parts by weight: 100 parts of copolymerized polypropylene and 30-60 parts of POE foaming masterbatch; the POE foaming masterbatch is composed of the following raw materials in parts by weight: 100 parts of POE particles, 6-15 parts of food-grade sodium bicarbonate, and 3-10 parts of fatty alcohol polyoxyethylene ether;

[0009] The micro-foamed cycloolefin copolymer is composed of the following raw materials in parts by weight: 100 parts of cycloolefin copolymer and 30-60 parts of POE foaming masterbatch; the POE foaming masterbatch is composed of the following raw materials in parts by weight: 100 parts of POE particles, 6-15 parts of food-grade sodium bicarbonate and 3-10 parts of fatty alcohol polyoxyethylene ether.

[0010] Further, as a preference, the copolymerized polypropylene has a melt flow rate of 1.2 g / min-1.8 g / min, a tensile strength of 25-30 MPa, an elongation at break greater than 90%, and an impact strength of 7-9 kJ / m 2 .

[0011] Further, as a preference, the diameter of the POE foaming masterbatch is 1-2 mm, and the mass density is 0.5-1 g / cm 3 .

[0012] Furthermore, as a preference, the POE particles have a melting temperature of 55-65°C, a melt index of 25-35 g / 10 min, and a mass density of 0.6-0.95 g / cm 3 .

[0013] Furthermore, preferably, the molecular weight of the fatty alcohol polyoxyethylene ether is 1000-1500.

[0014] Furthermore, preferably, the micro-foamed polypropylene has a pore size of 30-40 μm and a porosity of 25-35%.

[0015] The present invention also provides a method for preparing tableware containing micro-foam material, comprising the following steps:

[0016] S1: Preparation of POE foaming masterbatch: weigh 100 parts of POE particles, 6-15 parts of food-grade sodium bicarbonate, and 3-10 parts of fatty alcohol polyoxyethylene ether, stir the materials evenly, and then perform internal mixing and internal mixing, and then perform extrusion granulation;

[0017] S2: preparing micro-foamed material particles: weighing 100 parts of copolymerized polypropylene and 30-60 parts of POE foaming masterbatch obtained in step S1, and mixing the two thoroughly to obtain micro-foamed polypropylene particles; or weighing 100 parts of cycloolefin copolymer and 30-60 parts of POE foaming masterbatch obtained in step S1, and mixing the two thoroughly to obtain micro-foamed cycloolefin copolymer particles;

[0018] S3: homopolymer polypropylene is weighed and placed in one extruder, and the micro-foamed polypropylene particles prepared in S2 are placed in another extruder, and co-extruded into a three-layer sheet, wherein the inner and outer layers are homopolymer polypropylene, and the middle layer is micro-foamed polypropylene;

[0019] Alternatively, polyethylene is weighed and placed in one extruder, and the micro-foamed cycloolefin copolymer particles prepared in S2 are placed in another extruder, and co-extruded into a three-layer sheet, wherein the inner and outer layers are polyethylene respectively, and the middle layer is the micro-foamed cycloolefin copolymer particles;

[0020] S4: The sheet material obtained in S3 is blister-formed and punched into disposable tableware.

[0021] Furthermore, preferably, the thickness of the sheet extruded by S3 from inside to outside is 0.15-0.3 mm, 0.3-0.5 mm, and 0.15-0.3 mm, respectively.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The present invention adopts a sandwich structure, in which the middle layer is made of foam material, and the inner and outer layers are made of polyethylene or polypropylene. This can not only give the disposable tableware the physical properties of polyethylene / polypropylene such as rigidity and toughness, but also have the lightweight characteristics of foam material, and at the same time can also improve the thermal insulation performance of the tableware. Description of the drawings:

[0024] Figure 1 : It is a SEM scanning electron microscope image of the middle micro-foamed polypropylene layer of Example 1 in the present invention. Specific implementation method:

[0025] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments.

[0026] A brief summary of one or more aspects is given below to provide a basic understanding of these aspects. This summary is not an exhaustive overview of all conceived aspects, and is neither intended to identify the key or critical elements of all aspects nor to define the scope of any or all aspects. Its only purpose is to give some concepts of one or more aspects in a simplified form as a prelude to a more detailed description that will be given later.

[0027] Embodiment 1:

[0028] A tableware containing micro-foam material comprises an inner layer, an outer layer and a sandwich layer, wherein the sandwich layer is micro-foam polypropylene, and the inner layer and the outer layer are homopolymer polypropylene.

[0029] In this embodiment, the homopolymer polypropylene adopts the homopolymer polypropylene of Shenhua Ningxia 1102K, whose melt flow rate is 2.8g / 10min (230℃, 2.16Kg), tensile strength is 34MPa, elongation at break is greater than 50, and impact strength is 7.49kJ / m2 (23℃)

[0030] In this embodiment, the micro-foamed polypropylene is composed of the following raw materials in parts by weight: 100 parts of copolymerized polypropylene (each part is 1 kg, the same below), and 30 parts of POE foaming masterbatch; the POE foaming masterbatch is composed of the following raw materials in parts by weight: 100 parts of POE particles, 6 parts of food-grade sodium bicarbonate, and 5 parts of fatty alcohol polyoxyethylene ether.

[0031] The copolymer polypropylene adopts copolymer polypropylene with high melt strength, specifically E02ES from Zhenhai Petrochemical, with a melt flow rate of 1.5g / min (230℃, 2.16Kg), a tensile strength of 28.5MPa, an elongation at break>90, and an impact strength of 8.50kJ / m2 (23℃). Due to its low melt mass flow rate, it has high melt strength. The high melt strength caused by the branched structure in its molecules makes it difficult for the cells to merge or collapse during the foaming process with sodium bicarbonate chemical foaming agent.

[0032] POE particles are made of Dow 8400 ethylene-octene polymerized thermoplastic elastomer, which has a Vicat softening temperature of 41.0°C, a melting temperature of 60 degrees, a melt index of 30g / 10min, and a specific gravity of 0.87g / cm3. The purpose of selecting a melting point of around 60 degrees for POE is to prevent the food foaming agent from being pre-decomposed during the preparation of the foaming masterbatch. The high melt index makes the prepared masterbatch have a high melt index, which is conducive to uniform foaming of the masterbatch in PP.

[0033] Dow 8400POE has a narrow molecular weight distribution, low softening point, and high melt index (30g / 10min). At lower mixing temperatures, it can prevent the decomposition of sodium bicarbonate and has good fluidity and compatibility with polyolefins. In the case of a small amount of fatty alcohol polyoxyethylene ether dispersant (emulsifier), it can significantly improve the dispersion effect with materials such as foaming agents. POE also has a certain degree of adhesion, which is beneficial to the subsequent bonding performance as a sandwich layer with high-rigidity polypropylene film.

[0034] The molecular formula of fatty alcohol polyoxyethylene ether is C 58 H 118 O 24 , molecular weight is 1199.5431, melting point is 41-45℃, fatty alcohol polyoxyethylene ether effectively disperses the foaming agent in the masterbatch, and also plays a lubricating role, improving the melt index of the masterbatch. The high melt index allows the foaming masterbatch to be quickly dispersed in the copolymer polypropylene, making the pores uniform.

[0035] In this embodiment, a method for preparing tableware containing micro-foam material comprises the following steps:

[0036] S1: Preparation of POE foaming masterbatch: Weigh 100 parts of POE particles (each part is 1 kg, the same below), 6-15 parts of food-grade sodium bicarbonate, and 3-10 parts of fatty alcohol polyoxyethylene ether, stir the materials evenly, and then extrude and granulate them after internal mixing; the temperature of the internal mixer is controlled at about 60°C, and the speed is about 32r / min. During the internal mixing process, keep the equipment through cooling water to maintain the internal mixing temperature to prevent the decomposition of sodium bicarbonate. This temperature can melt POE but will not cause the decomposition of sodium bicarbonate. The internal mixing time is 30 minutes to allow the foaming agent to be evenly dispersed in POE;

[0037] S2: Preparation of micro-foamed polypropylene particles: Weigh 100 parts of copolymerized polypropylene and 30-60 parts of POE foaming masterbatch obtained in step S1, and mix the two thoroughly; the diameter of the obtained micro-foamed polypropylene particles is about 1-2 mm, and the mass density is 0.005-0.01 g / cm 3 ;

[0038] S3: homopolymer polypropylene is weighed and placed in one extruder, and the micro-foamed polypropylene particles obtained in S2 are placed in another extruder, and extruded into a three-layer sheet by co-extrusion, wherein the inner and outer layers are homopolymer polypropylene, and the middle layer is micro-foamed polypropylene. The heating temperature of the extruder is about 200°C, and the temperature of the extrusion die is about 210°C; the thicknesses of the three layers from the inside to the outside are 0.2mm, 0.4mm and 0.2mm, respectively, and the total thickness of the three-layer sheet is 0.80mm;

[0039] S4: punching the sheet material obtained in S3 into disposable tableware.

[0040] Embodiment 2:

[0041] Different from Example 1, the micro-foamed polypropylene is composed of the following raw materials in parts by weight: 100 parts of copolymerized polypropylene (each part is 1 kg, the same below), and 35 parts of POE foaming masterbatch; the POE foaming masterbatch is composed of the following raw materials in parts by weight: 100 parts of POE particles, 8 parts of food-grade sodium bicarbonate, and 3 parts of fatty alcohol polyoxyethylene ether.

[0042] The thickness of the three layers of the prepared sandwich structure sheet from the inside to the outside are 0.2 mm, 0.3 mm and 0.3 mm respectively, and the total thickness of the three-layer sheet is 0.80 mm.

[0043] Example 3A:

[0044] Different from Example 1, the micro-foamed polypropylene is composed of the following raw materials in parts by weight: 100 parts of copolymerized polypropylene (each part is 1 kg, the same below), and 40 parts of POE foaming masterbatch; the POE foaming masterbatch is composed of the following raw materials in parts by weight: 100 parts of POE particles, 10 parts of food-grade sodium bicarbonate, and 6 parts of fatty alcohol polyoxyethylene ether.

[0045] The thickness of the three layers of the prepared sandwich structure sheet from the inside to the outside are 0.15 mm, 0.5 mm and 0.15 mm respectively, and the total thickness of the three-layer sheet is 0.80 mm.

[0046] Example 3B:

[0047] Different from Example 3A, the thickness of the three layers of the sandwich structure sheet from the inside to the outside are 0.2 mm, 0.4 mm and 0.2 mm respectively, and the total thickness of the three-layer sheet is 0.80 mm.

[0048] Embodiment 4:

[0049] Different from Example 1, the micro-foamed polypropylene is composed of the following raw materials in parts by weight: 100 parts of copolymerized polypropylene (each part is 1 kg, the same below), and 50 parts of POE foaming masterbatch; the POE foaming masterbatch is composed of the following raw materials in parts by weight: 100 parts of POE particles, 13 parts of food-grade sodium bicarbonate, and 8 parts of fatty alcohol polyoxyethylene ether.

[0050] The thickness of the three layers of the prepared sandwich structure sheet from the inside to the outside are 0.3 mm, 0.2 mm and 0.3 mm respectively, and the total thickness of the three-layer sheet is 0.80 mm.

[0051] Embodiment 5:

[0052] Different from Example 1, the micro-foamed polypropylene is composed of the following raw materials in parts by weight: 100 parts of copolymerized polypropylene (each part is 1 kg, the same below), and 50 parts of POE foaming masterbatch; the POE foaming masterbatch is composed of the following raw materials in parts by weight: 100 parts of POE particles, 15 parts of food-grade sodium bicarbonate, and 10 parts of fatty alcohol polyoxyethylene ether.

[0053] The thickness of the three layers of the prepared sandwich structure sheet from the inside to the outside are 0.2 mm, 0.4 mm and 0.2 mm respectively, and the total thickness of the three-layer sheet is 0.80 mm.

[0054] The raw materials of Examples 1-5 are shown in Table 1 below:

[0055]

[0056] Comparative Example 1:

[0057] As a comparison, homopolymer polypropylene was used as raw material, Shenhua Ningxia 1102K was extruded into sheets with a thickness of 0.8 mm, and then stamped into disposable tableware.

[0058] Examples 1-5 and Comparative Example 1 were punched into lunch boxes with a size of 200 mm×200 mm×400 mm for testing. The test results are shown in Table 2 below:

[0059]

[0060] Weight test method: 100 lunch boxes with a size of 200 mm × 200 mm × 400 mm were prepared in Examples 1-5 and Comparative Example 1 respectively, and the weights were measured;

[0061] Tensile strength test: Test the tensile strength of the entire sheet in accordance with GB / T1040;

[0062] Impact strength test: Test the tensile strength and impact strength of the entire sheet in accordance with GB8809-2015;

[0063] The cooling time refers to the cooling temperature of the material after extrusion of S3 in Examples 1-5 and the cooling time of the material after extrusion of Comparative Example 1.

[0064] The lunch boxes made in Examples 1-5 and Comparative Example 1 are all smooth and clean, with uniform texture, no wrinkles or scratches, and no burrs or the like on the edges.

[0065] From the above test results, the weight of each 100 pieces of disposable tableware with a "sandwich" structure is significantly reduced, and the maximum weight reduction is 38.9% compared with Comparative Example 1;

[0066] Comparing Example 3A with Example 3B, under the same other conditions, the decrease in weight is related to the thickness of the middle layer. The thicker the middle layer, the lighter the weight of the disposable tableware. This is mainly due to the use of micro-foamed polypropylene in the middle layer.

[0067] At the same time, the cooling time of disposable tableware with a "sandwich" structure is significantly prolonged, which means it has better thermal insulation performance, and the thermal insulation performance is also related to the thickness of the second layer.

[0068] In terms of mechanical properties, the tensile strength of the "sandwich" structure decreases slightly, especially in Example 5. This may be mainly due to the addition of more foaming masterbatch, which leads to an increase in the number of micro-foamed polypropylene cells. But in general, the tensile strength of each embodiment meets the technical requirements of the disposable tableware industry.

[0069] From the perspective of impact strength performance, the impact strength of each embodiment is improved to varying degrees compared with the comparative example. This is mainly due to the high impact strength of the E02ES copolymer PP itself, and the impact strength of the tableware with a "sandwich" structure is improved to a certain extent.

[0070] Embodiment 6:

[0071] A tableware containing micro-foam material comprises an inner layer, an outer layer and a sandwich layer, wherein the sandwich layer is micro-foam cycloolefin copolymer (COC), and the inner layer and the outer layer are polyethylene.

[0072] In this embodiment, the polyethylene is selected from low-density polyethylene (LDPE), preferably Yangzi Petrochemical LDPE7042, which has a melt flow rate of 1.7-2.3g / 10min (230°C, 2.16Kg), a tensile strength of 18-25MPa, an elongation at break >300%, a hardness (Shore) of 45-65, and a flexural modulus of 1500mPa.

[0073] In this embodiment, the micro-foamed COC is composed of the following raw materials in parts by weight: 100 parts of COC (each part is 1 kg, the same below), 30 parts of POE foaming masterbatch; the POE foaming masterbatch is composed of the following raw materials in parts by weight: 100 parts of POE particles, 6 parts of food-grade sodium bicarbonate, and 5 parts of fatty alcohol polyoxyethylene ether.

[0074] Among them, COC is selected from high-rigidity and high-strength COC, preferably German 6017, and more preferably COC residue from biomedical manufacturing, with a melt flow rate of 1.5g / 10min (230°C, 2.16Kg), a tensile strength of 58MPa, a tensile elongation of 2.4%, and a flexural modulus of >3000mPa.

[0075] The POE particles are the same as those in Example 1.

[0076] Fatty alcohol polyoxyethylene ether is the same as in Example 1.

[0077] In this embodiment, a method for preparing tableware containing micro-foam material comprises the following steps:

[0078] S1: Preparation of POE foaming masterbatch: Weigh 100 parts of POE particles (each part is 1 kg, the same below), 6 parts of food-grade sodium bicarbonate, and 5 parts of fatty alcohol polyoxyethylene ether, stir the materials evenly, and then extrude and granulate them after internal mixing; the temperature of the internal mixer is controlled at about 60°C, and the speed is about 32r / min. During the internal mixing process, keep the equipment through cooling water to maintain the internal mixing temperature to prevent the decomposition of sodium bicarbonate. This temperature can melt POE but will not cause the decomposition of sodium bicarbonate. The internal mixing time is 30 minutes to allow the foaming agent to be evenly dispersed in POE;

[0079] S2: Preparation of micro-foamed COC particles: weigh 100 parts of German 6017 residue and 30 parts of POE foaming masterbatch obtained in step S1, and mix the two thoroughly;

[0080] S3: Weigh polyethylene and place it in one extruder. Place the micro-foamed COC particles obtained in S2 in another extruder and extrude them into a three-layer sheet by co-extrusion, wherein the inner and outer layers are polyethylene, and the middle layer is micro-foamed COC. The heating temperature of the extruder is about 200°C, and the temperature of the extrusion die is about 210°C. The thicknesses of the three layers from the inside to the outside are 0.1mm, 0.2mm and 0.1mm, respectively, and the total thickness of the three-layer sheet is 0.40mm.

[0081] S4: punching the sheet material obtained in S3 into disposable tableware.

[0082] Embodiment 7:

[0083] Different from Example 6, the micro-foamed COC is composed of the following raw materials in parts by weight: 100 parts of COC particles (1 kg each, the same below), and 35 parts of POE foaming masterbatch; the POE foaming masterbatch is composed of the following raw materials in parts by weight: 100 parts of POE particles, 8 parts of food-grade sodium bicarbonate, and 3 parts of fatty alcohol polyoxyethylene ether.

[0084] The thickness of the three layers of the prepared sandwich structure sheet from the inside to the outside are 0.2 mm, 0.1 mm and 0.1 mm respectively, and the total thickness of the three-layer sheet is 0.40 mm.

[0085] Embodiment 8:

[0086] Different from Example 6, the micro-foamed COC is composed of the following raw materials in parts by weight: 100 parts of COC particles (1 kg each, the same below), 40 parts of POE foaming masterbatch; the POE foaming masterbatch is composed of the following raw materials in parts by weight: 100 parts of POE particles, 10 parts of food-grade sodium bicarbonate, and 6 parts of fatty alcohol polyoxyethylene ether.

[0087] The thickness of the three layers of the prepared sandwich structure sheet from the inside to the outside are 0.15 mm, 0.1 mm and 0.15 mm respectively, and the total thickness of the three-layer sheet is 0.40 mm.

[0088] Embodiment 9:

[0089] Different from Example 6, the micro-foamed COC is composed of the following raw materials in parts by weight: 100 parts of COC particles (1 kg each, the same below), 50 parts of POE foaming masterbatch; the POE foaming masterbatch is composed of the following raw materials in parts by weight: 100 parts of POE particles, 13 parts of food-grade sodium bicarbonate, and 8 parts of fatty alcohol polyoxyethylene ether.

[0090] The thickness of the three layers of the prepared sandwich structure sheet from the inside to the outside are 0.2 mm, 0.1 mm and 0.1 mm respectively, and the total thickness of the three-layer sheet is 0.40 mm.

[0091] Example 10A:

[0092] Different from Example 6, the micro-foamed COC is composed of the following raw materials in parts by weight: 100 parts of COC particles (1 kg each, the same below), and 60 parts of POE foaming masterbatch; the POE foaming masterbatch is composed of the following raw materials in parts by weight: 100 parts of POE particles, 15 parts of food-grade sodium bicarbonate, and 10 parts of fatty alcohol polyoxyethylene ether.

[0093] The thickness of the three layers of the prepared sandwich structure sheet from the inside to the outside are 0.1 mm, 0.2 mm and 0.1 mm respectively, and the total thickness of the three-layer sheet is 0.40 mm.

[0094] Example 10B:

[0095] The thickness of the three layers of the prepared sandwich structure sheet from the inside to the outside are 0.2 mm, 0.1 mm and 0.1 mm respectively, and the total thickness of the three-layer sheet is 0.40 mm.

[0096] The raw materials of Examples 6-10 are shown in Table 3 below:

[0097]

[0098]

[0099] Comparative Example 2:

[0100] In comparison, Yangzi Petrochemical LDPE7042 polyethylene granules were used as raw materials to extrude sheets with a thickness of 0.4 mm and then punched into disposable tableware.

[0101] Examples 6-10 and Comparative Example 2 were punched into lunch boxes with a size of 200 mm × 200 mm × 400 mm for testing, 100 of each were tested, and the average value was taken. The test results are shown in Table 4 below:

[0102]

[0103] Tensile strength test: Test the tensile strength of the entire sheet in accordance with GB / T1040;

[0104] Bending modulus test: Test the bending modulus of the whole sheet in accordance with GB / T9341-2008;

[0105] Load test: 500g of rice is stored in a disposable box, which is sealed with PE film. Six disposable boxes are stacked and the appearance of the boxes is observed after 1 hour.

[0106] The lunch boxes made in Examples 6-10 and Comparative Example 2 are all smooth and clean, with uniform texture, no wrinkles or scratches, and no burrs or the like on the edges.

[0107] From the above test results, it can be seen that the bending modulus of disposable tableware with a "sandwich" structure is significantly higher than that of comparative example 1, which is mainly due to the high rigidity and high strength of COC.

[0108] Comparing the bending strength data of each embodiment, under the condition of the same thickness of the second layer, as the amount of foaming masterbatch increases, the bending modulus tends to gradually decrease. This is mainly because as the amount of foaming masterbatch increases, the amount of COC cells increases, resulting in a decrease in the bending modulus.

[0109] Comparing Example 10A and Example 10B, under the same other conditions, the thicker the second layer, the greater its bending modulus. This is mainly because the second layer uses high-rigidity and high-strength micro-foamed COC.

[0110] The change in tensile strength of each embodiment and comparative example 2 is generally the same as the change trend of the bending modulus, that is, the tensile strength is improved overall, and as the thickness of the second layer increases, the increase in tensile strength is more obvious, and as the amount of foaming masterbatch increases, the tensile strength decreases. However, in general, the tensile strength of each embodiment is relatively high, which fully meets the technical requirements of disposable food packaging boxes.

[0111] The load test results show that due to the strong support of the high-rigidity and high-strength COC sandwich layer, the disposable food packaging box does not collapse and the user experience is better.

[0112] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.

Claims

1. A tableware containing micro-foam material, characterized in that: It comprises an inner layer, an outer layer and a sandwich layer, wherein the sandwich layer is made of micro-foam material, and the inner layer and the outer layer are made of homopolymer polypropylene or polyethylene.

2. The tableware containing micro-foam material according to claim 1, characterized in that: The homopolymer polypropylene has a melt flow rate of 2.0 g / 10 min-3.0 g / 10 min, a tensile strength of 30-40 MPa, an elongation at break greater than 50%, and an impact strength of 6-8 kJ / m 2 .

3. The tableware containing micro-foam material according to claim 1, characterized in that: The micro-foam material is micro-foam polypropylene or micro-foam cycloolefin copolymer; the micro-foam polypropylene is composed of the following raw materials in parts by weight: 100 parts of copolymerized polypropylene and 30-60 parts of POE foaming masterbatch; the POE foaming masterbatch is composed of the following raw materials in parts by weight: 100 parts of POE particles, 6-15 parts of food-grade sodium bicarbonate, and 3-10 parts of fatty alcohol polyoxyethylene ether; The micro-foamed cycloolefin copolymer is composed of the following raw materials in parts by weight: 100 parts of cycloolefin copolymer and 30-60 parts of POE foaming masterbatch; the POE foaming masterbatch is composed of the following raw materials in parts by weight: 100 parts of POE particles, 6-15 parts of food-grade sodium bicarbonate and 3-10 parts of fatty alcohol polyoxyethylene ether.

4. The tableware containing micro-foam material according to claim 3, characterized in that: The copolymer polypropylene has a melt flow rate of 1.2 g / min-1.8 g / min, a tensile strength of 25-30 MPa, an elongation at break greater than 90%, and an impact strength of 7-9 kJ / m 2 .

5. The tableware containing micro-foam material according to claim 3, characterized in that: The diameter of the POE foaming masterbatch is 1-2 mm, and the mass density is 0.5-1 g / cm 3 .

6. The tableware containing micro-foam material according to claim 3, characterized in that: The POE particles have a melting temperature of 55-65°C, a melting index of 25-35 g / 10 min, and a mass density of 0.6-0.95 g / cm 3 .

7. The tableware containing micro-foam material according to claim 3, characterized in that: The molecular weight of the fatty alcohol polyoxyethylene ether is 1000-1500.

8. The tableware containing micro-foam material according to claim 3, characterized in that: The micro-foamed polypropylene has a pore size of 30-40 μm and a porosity of 25-35%.

9. A method for preparing tableware containing micro-foam material, characterized in that: The following steps are involved: S1: Preparation of POE foaming masterbatch: weigh 100 parts of POE particles, 6-15 parts of food-grade sodium bicarbonate, and 3-10 parts of fatty alcohol polyoxyethylene ether, stir the materials evenly, and then perform internal mixing and internal mixing, and then perform extrusion granulation; S2: preparing micro-foamed material particles: weighing 100 parts of copolymerized polypropylene and 30-60 parts of POE foaming masterbatch obtained in step S1, and mixing the two thoroughly to obtain micro-foamed polypropylene particles; or weighing 100 parts of cycloolefin copolymer and 30-60 parts of POE foaming masterbatch obtained in step S1, and mixing the two thoroughly to obtain micro-foamed cycloolefin copolymer particles; S3: homopolymer polypropylene is weighed and placed in one extruder, and the micro-foamed polypropylene particles prepared in S2 are placed in another extruder, and co-extruded into a three-layer sheet, wherein the inner and outer layers are homopolymer polypropylene, and the middle layer is micro-foamed polypropylene; Alternatively, polyethylene is weighed and placed in one extruder, and the micro-foamed cycloolefin copolymer particles prepared in S2 are placed in another extruder, and co-extruded into a three-layer sheet, wherein the inner and outer layers are polyethylene respectively, and the middle layer is the micro-foamed cycloolefin copolymer particles; S4: The sheet material obtained in S3 is blister-formed and punched into disposable tableware.

10. The method for preparing tableware containing micro-foam material according to claim 9, characterized in that: The thickness of the sheet extruded by S3 from inside to outside are 0.15-0.3mm, 0.3-0.5mm, and 0.15-0.3mm respectively.

Citation Information

Patent Citations

  • Polyolefin foaming masterbatch composition and preparation method and application

    CN106432887A

  • Foam sheet comprising skin layer, method for manufacturing same, and food container comprising same

    CN111629895A

  • Foamed polypropylene composite material with good appearance as well as preparation method and application of foamed polypropylene composite material

    CN117467220A

  • Polymer foams

    CN1202188A

  • Three lager coextrusion foamed board and its use and preparation method

    CN1590070A